BĐT nha mn
CMR:Với mọi số thực $a_1,a_2,....a_
{2n
} và b_1,b_2,....b_
{2n
}.ta có BĐT\sum_{k=1}^{2n}a_k^{2}\sum_{k=1}^{2n}b_k^{2} -(\sum_{k=1}^{n}(a_
{2k
} b_{2k-1} -a_{2k-1}b_{2k}))^{2}\geq (\sum_{k=1}^{2n}a_k b_k)^{2} $
Bất đẳng thức
BĐT nha mn
CMR:Với mọi số thực
a_1,a_2,....a_2n và
b_1,b_2,....b_2n.ta có BĐT
\sum_{k=1}^{2n}a_k^{2}\sum_{k=1}^{2n}b_k^{2} -(\sum_{k=1}^{n}(a_2k b_{2k-1} -a_{2k-1}b_{2k}))^{2}\geq (\sum_{k=1}^{2n}a_k b_k)^{2}
Bất đẳng thức
BĐT nha mn
CMR:Với mọi số thực $a_1,a_2,....a_
{2n
} và b_1,b_2,....b_
{2n
}.ta có BĐT\sum_{k=1}^{2n}a_k^{2}\sum_{k=1}^{2n}b_k^{2} -(\sum_{k=1}^{n}(a_
{2k
} b_{2k-1} -a_{2k-1}b_{2k}))^{2}\geq (\sum_{k=1}^{2n}a_k b_k)^{2} $
Bất đẳng thức